2015
DOI: 10.1016/j.ijbiomac.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and properties of gelatin from skin of seabass with different sizes

Abstract: Gelatin was extracted from the skin of seabass (Lutes calcarifer) with different average sizes (2, 4 and 6 kg/fish), termed G2, G4 and G6, respectively and their characteristics and functional properties were determined. Yields of G2, G4 and G6 were 38.22, 40.50 and 43.48% (based on dry weight), respectively. G2 contained cc-chains as dominant component, whilst G4 and G6 comprised alpha-, beta- and gamma-chains with a larger content of high MW cross-links. All gelatins had the similar imino acid (hydroxyprolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…With increase in temperature and time of extraction, destabilization of bonds between α-chains of the native collagen molecules occurs. [4] This results in higher recovery of gelatin. In the present study, a temperature of 85°C for 60 min yielded 7.15%.…”
Section: Gelatin Yieldmentioning
confidence: 99%
See 4 more Smart Citations
“…With increase in temperature and time of extraction, destabilization of bonds between α-chains of the native collagen molecules occurs. [4] This results in higher recovery of gelatin. In the present study, a temperature of 85°C for 60 min yielded 7.15%.…”
Section: Gelatin Yieldmentioning
confidence: 99%
“…[17] But at the same time, the properties such as bloom value, viscosity and colour were found to diminish. [4,17] The yield of gelatin from acid and alkali pre-treated skins of bigeye snapper, tiger-toothed croaker, and sin croaker was 4, 7.56, and 14.3%, respectively. [13,14,25] Mohtar et al [10] reported 17.6% of yield from hoki skins pre-treated with 0.75 M NaCl.…”
Section: Gelatin Yieldmentioning
confidence: 99%
See 3 more Smart Citations